Three-dimensional motion analysis for validation of shoulder internal rotation - Maier, Michael Wolfgang; Erhard, Sarah; Thielen, Mirjam; Bruckner, Thomas; Wolf, Sebastian Immanuel; Zeifang, Felix; Raiss, Patric (Archives of orthopaedic and trauma surgery, 2017)
Background10% of the points for the Constant-Murley score (CMS) are allocated for the capacity for internal rotation (IR), measured as unassisted active movement of the dorsum of the hand or the thumb to reach different anatomical landmarks. However, there is little information about the validity of this method and no three-dimensional measurement of the degree of IR that is necessary to reach these landmarks.MethodsSixteen volunteers with healthy shoulders were recruited. The degree of IR was defined using the following landmarks as described in the CMS: (1) lateral aspect of thigh, (2) buttock, (3) sacroiliac joint, (4) level of waist, (5) vertebra T12, (6) interscapular. The validity of IR measurement was assessed by simultaneous 3D motion analysis.ResultsUsing the thumb as pointer, there were significant increases in IR from 39.3° at position 1 to 80.4° at position 2, followed by 105.1°, 108.6°, 110.1°, and 125.3° at position 3-6. Taking the dorsum of the hand as pointer, there were significant increases in IR between all positions, starting from 71.2° (position 1) and followed by 99.3°, 104.1°, 110.3°, 115.2°, and 119.7° at positions 2 to 6. Comparing the two measurement methods, a significant difference was found for the amount of IR between positions 1 and 2.ConclusionMeasurement of IR as described in the CMS is a suitable method. However, there was an increase of only 10° in IR between positions 3 and 5, which may be hard to measure with a standard goniometer in clinical practice.